A lattice Boltzmann study of frost growth on a cold surface. (November 2018) - Gong, Jianying; Hou, Jianqiang; Li, Guojun; Gao, Tieyu; Sun, Jinjuan
Abstract: A two-dimensional Lattice Boltzmann model was established to study the dynamic physical process of frost growth on a cold flat surface. It is verified that the theoretical results are in good agreement with the experiment data with better accuracy. The frost morphology is explored by showing two-dimension density distribution with different cold surface temperatures. The results also include dynamic characteristics of frost properties such as thickness, deposition weight, volume fraction, density, temperature. According to the results, it is found that the nearer it is from the cold flat plate, the larger of frost crystal volume fraction and density are. The frost surface temperature increases rapidly at the early period of frosting and then increases gradually towards the triple point temperature of the water. The frost internal temperatures rise in a linear tendency with the frost thickness and decrease at the same frost layer location with frost growth. Super-saturation degree of moist air has non-negligible effect on frost growth parameters such as frost thickness, frost crystal deposition mass, frost deposition rate and frost crystal volume fraction.